The mediating role of social media disorder in the relationship between social media use and self-harm behavior in Indonesian adolescents - Kaligis, Fransiska; Adnyani, Cokorda Istri Agung Dewinta; Wikanta, Kevin Girisamudra; Darmawan, Muhammad Dzaky; Reza, Muhammad; Pramatirta, Billy; Masiran, Ruziana (Frontiers in Public Health, 2025)
IntroductionSocial media use in adolescence has been at an all-time high, along with the constant increase of self-harm behavior. Existing research on the relationship between social media usage and self-harm behavior in adolescent is inconsistent and scarce. We aimed to determine the relationship between adolescent self-harm behavior and social media usage, as well as to explore the mediating role of social media disorder in the relationship between social media use and self-harm behavior in Indonesian adolescents.MethodA cross-sectional study was conducted to investigate the relationship between self-harm behavior and social media use in 1096 adolescents aged 13–18 years old, who attend secondary and high schools in Jakarta.ResultsHigher social media usage intensity was significantly correlated with increased instances of self-harm (p < 0.001). Similarly, a significant association was found between social media disorder and self-harm behavior (p < 0.001). Confirmatory Factor Analysis (CFA) yielded an acceptable and good fit of latent construct modeling based on several indices. Regression analysis indicated a strong link between social media usage time and social media disorder (β = 0.277, p = 0.035), and between social media disorder and self-harm behavior (β = 0.353, p < 0.001).ConclusionSocial media usage intensity and social media disorder was associated with self-harm behavior in adolescents, with social media disorder partially mediating the link between social media usage intensity and self-harm behavior. Our findings emphasize the importance of monitoring and managing social media use among adolescents to mitigate the risk of self-harm.